Site-directed mutagenesis in Brucella abortus S19 by overlap extension PCR-based procedure - NAYERI FASAEI, B.; ZAHRAEI SALEHI, T.; NASERLI, S.; SAEEDINIA, A. R; BEHROOZIKHAH, A. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Introduction of a site-directed mutation can be effective method to evaluate properties of various genes. Brucellosis is one of the most common zoonotic infectious diseases, which causes great economic losses. Thus, determination of pathogenicity factors in the genus Brucella can lead to the control of this health problem. Due to the importance of site-directed mutations in identification of genomic structure, overlap extension polymerase chain reaction (PCR) has been introduced as an improved technique for the removal and replacement of gene targets. In this study, three DNA fragments were amplified and combined using a two-step PCR with specific primers. The resulting fusion PCR product, obtained without any change in the nucleotide sequence, was cloned in a specific position in the pBluescript II SK (-) plasmid using restriction enzymes. Finally, the construct was transferred into cells of Brucella abortus S19 by electroporation and replaced the target gene (wbkA) in the genome of the bacterium. PCR analysis was performed on kanamycin-resistant colonies to provide genetic evidence that the B. abortus wbkA gene was interrupted by the kanamycin cassette. The results of this study show that the optimized modified technique, splicing by overlap extension PCR, is effective in creating mutations in the bacterial genome and can easily be used in Brucella spp.